1985
DOI: 10.1073/pnas.82.2.548
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and protective mechanisms in erythrocytes in relation to Plasmodium vinckei load.

Abstract: The protection of mouse erythrocytes (RBC) parasitized with Plasmodium vinckei vinckei against activated oxygen species was examined in relation to the intraerythrocytic parasite load. RBC from highly infected annials were separated by density gradient centrifugation into six bands with increasing parasite content and with parasitemias ranging from 17% to 100%. Increase in parasite load was accompanied by a decrease in the activities of the enzymes superoxide dismutase (EC 1.15.1.1), catalase (EC 1.11.1.6), gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…When BODIPY 581/591-PC was used to probe P. falciparum-infected RBCs, we found an increase in the level of conversion of the chromophore to the oxidized form as the parasite matures. These data are consistent with previous studies indicating an overall increase in oxidative damage in infected RBCs (2,22,60), although these previous results could have been affected by inadvertent oxidation during sample work up (61). The increase in oxidative stress experienced by trophozoite-infected RBCs would be expected to increase their susceptibility to antimalarial drugs such as chloroquine that increase the levels of free FP-FeIII and are likely to exacerbate oxidative stress.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…When BODIPY 581/591-PC was used to probe P. falciparum-infected RBCs, we found an increase in the level of conversion of the chromophore to the oxidized form as the parasite matures. These data are consistent with previous studies indicating an overall increase in oxidative damage in infected RBCs (2,22,60), although these previous results could have been affected by inadvertent oxidation during sample work up (61). The increase in oxidative stress experienced by trophozoite-infected RBCs would be expected to increase their susceptibility to antimalarial drugs such as chloroquine that increase the levels of free FP-FeIII and are likely to exacerbate oxidative stress.…”
Section: Discussionsupporting
confidence: 82%
“…By contrast, other studies find an increase in tocopherol levels and no evidence for lipid oxidation, unless additional oxidative stress is applied (2,23). In this work, we have used BODIPY 581/591-PC and novel imaging and flow cytometry formats to reexamine oxidative stress in P. falciparum-infected RBCs.…”
mentioning
confidence: 99%
“…Where possible, numbers are given for the first and last amino acid residue of each secondary-structure element. that several factors contribute to the formation of methemoglobin during plasmodial infection, including the acidic pH of the plasmodial food vacuole, oxidative damage within infected erythrocytes (51,52), and the reduced activity of NADH-methemoglobin reductase (53). A significantly increased methemoglobin content in the range of 20 -42% has been detected in the plasmodial food vacuole compared with 0.6 -1.0% in uninfected erythrocytes (51).…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide dismutase (EC 1.15.1.1; SOD) catalyses the dismutation of superoxide anions (02-) to H 2 0 2 and O2 while catalase (EC 1.11.1.6) and glutathione peroxidase (EC 1.1 1.1.9; GPx) break down H 2 0 2 to water and 0 2 (Fairfield et al 1988). Several studies have reported on the antioxidantdefence enzymes in plasmodium-infected and uninfected erythrocytes (Suthipark et al 1982;Seth et al 1985;Stocker et al 1985). However, the role of riboflavin has not been studied.…”
mentioning
confidence: 99%